PENGARUH MODEL PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT TERHADAP SIKAP ILMIAH DAN PRESTASI BELAJAR IPA PADA SISWA KELAS V SDN GUGUS BANYUNING - Ni Nyoman Lisna Handayani; Ni Ketut Erna Muliastrini (Padma Sari: Jurnal Ilmu Pendidikan, 2021)
This research aims to investigate the effect of Community-Science- Technology learning approach toward scientific attitude and science learning achievement on fifth grade students of public elementary school Banyuning Cluster. This research was a quasi-experiment with Posttest-Only Control-Group Design. Research population was 198 fifth grade students of Belantih cluster. Thirty three students were selected as sample which was determined using random sampling technique. Scientific attitude data were gathered using questionnaire and science learning achievement data were gathered using multiple choice test. Data were analyzed using MANOVA (Multivariate Analysis of Variance) assisted by SPSS 17.00 for windows. Research results show that: First, scientific attitude of students who followed Community-Science-Technology learning approach was significantly better than students who followed conventional learning. Second, science learning achievement of students who followed community-science-technology learning approach was significantly better than students who followed conventional learning. Third, simultaneously, scientific attitude and science learning achievement of students who followed community-science- technology learning approach was significantly better than students who followed conventional learning. The results of this study are expected to provide information for educational institutions to take appropriate policies, which are related to efforts to develop scientific attitudes and improve student learning outcomes.